Information Needs and Seeking Behaviour of Village Library Users - Dev Singh, Gur; Kumar, Anil (Journal of Information and Knowledge, 2019)
The present survey deals with information needs and seeking behavior of library users of Goli Village of Karnal District. To identify the purposes of seeking information and preferred information sources, a survey using a structured questionnaire was conducted. A sample of 150 users of Goli village library was selected using purposive sampling technique to collect the required data. Out of 150 questionnaires, 142 filled in questionnaires were returned. It was found that most users of the village library are men and not many women used the library. The study reveals that majority of respondents sought information on jobs/recruitment, general knowledge and news update (92.96 percent) and education (84.51 percent) related information.